2022
DOI: 10.1186/s12891-022-05040-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiologic outcomes in patients undergoing primary total hip arthroplasty with Collum Femoris Preserving stems: a comparison between the direct anterior approach and the posterior approach

Abstract: Background The direct anterior approach (DAA) and posterior approach (PA) are two of the most common surgical approaches used for total hip arthroplasty (THA) worldwide. The curved anatomical collum femoris-preserving (CFP) stem was designed to preserve the bone of the femoral neck and allow physiologic load transfer along the trabecular systems, which may better restore hip biomechanics, improve triplanar stem stability and improve the long-term survival rate. We believe this study will demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The Forgotten Joint Score (FJS-12) was evaluated by a total of 3 articles comparing DAA versus PA (Table 1). 19,20,27 Though the FJS-12 scores tended to favour DAA, pooled data from all 3 of these studies demonstrated no significant differences in FJS-12 scores between the DAA and PA group (MD 5.88; 95% CI, −0.36–12.12; p = 0.06) (Figure 7).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The Forgotten Joint Score (FJS-12) was evaluated by a total of 3 articles comparing DAA versus PA (Table 1). 19,20,27 Though the FJS-12 scores tended to favour DAA, pooled data from all 3 of these studies demonstrated no significant differences in FJS-12 scores between the DAA and PA group (MD 5.88; 95% CI, −0.36–12.12; p = 0.06) (Figure 7).…”
Section: Resultsmentioning
confidence: 96%
“…Utilising the pre-determined inclusion and exclusion criteria, 24 articles were included in the final analysis. 1639 Each article’s reference list was evaluated in a stepwise manner, and no additional studies were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its introduction, many clinical workers have used it as an important indicator of the maximum satisfaction and surgical success of patients after hip replacement surgery [8,9] . Previous studies have shown that compared to PA, DAA can achieve better FJS, but the conclusions of different studies are not consistent [10][11][12][13][14][15][16] . Currently, there is no evidence from systematic reviews on this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…During the initial stages of this learning curve, surgeons may encounter technical challenges that could influence surgical outcomes, including the incidence of complications. However, as the surgeon's proficiency improves, these differences may gradually diminish until reaching a similar level ( 10 ). In our study, the surgical method chosen by our surgeons was the Posterior Approach, and they had already overcome the learning curve, possessing extensive experience with this approach.…”
Section: Introductionmentioning
confidence: 99%